2015
DOI: 10.1111/ijd.12784
|View full text |Cite
|
Sign up to set email alerts
|

Occupational toxic epidermal necrolysis associated with dalbergia cochinchinensis: a retrospective comparative study of eight cases in China

Abstract: Occupational TEN has a longer progression than TEN caused by drugs, and there is more difficulty in its treatment. Clinicians should pay attention to this disease. However, its mechanism and target therapy remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In addition, the evaluation of combined therapies is more prone to errors than that of a single treatment. The results of this study suggest a reduction in mortality in patients treated with combined IVIG + CE therapy compared to those treated only with CE, 25,38,55,60‐62 IVIG alone 25 or just compared to the predicted mortality 41,63,64 . The EuroSCAR cohort study found a lower mortality in 40 patients treated with IVIG + CE compared with 35 patients treated with IVIG alone (mortality 18% vs 34%, respectively) 53 .…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the evaluation of combined therapies is more prone to errors than that of a single treatment. The results of this study suggest a reduction in mortality in patients treated with combined IVIG + CE therapy compared to those treated only with CE, 25,38,55,60‐62 IVIG alone 25 or just compared to the predicted mortality 41,63,64 . The EuroSCAR cohort study found a lower mortality in 40 patients treated with IVIG + CE compared with 35 patients treated with IVIG alone (mortality 18% vs 34%, respectively) 53 .…”
Section: Discussionmentioning
confidence: 64%
“…3 Obat penyebab tersering adalah obat antiinflamasi nonsteroid (OAINS), 4,5 golongan sulfa, 6,7 antibiotik laktam, antikonvulsan (misalnya karbamazepin, fenobarbital, dan fenitoin), antiretrovirus, agen kontras, alopurinol, dan lainlain. 8,9 Kerusakan jaringan pada NE terjadi akibat apoptosis sel keratinosit yang diinduksi oleh stimulus stres, kerusakan DNA, dan sitokin intraselular. 2,3 Insidens terjadinya SSJ diperkirakan 1-6,5 kasus per juta orang per tahun.…”
Section: Pendahuluanunclassified
“…Chemical constituents from the heartwood of D. cochinchinensis were isolated [7][8][9], e.g., 6,4 -dihydroxy-7-methoxyflavan [9]. From a clinical perspective, occupational toxic epidermal necrolysis was associated with D. cochinchinensis [10], and some compounds showed inhibitory activity towards 5α-dihydrotestosterone [9].The impact of isolated compounds of D. cochinchinensis to modulate an inflammatory response is rather unknown.…”
Section: Introductionmentioning
confidence: 99%